Endobronchial blocker and extracorporeal membrane oxygenation use for lung abscess complicated by a bronchopleural fistula in a pediatric patient: a case report and literature review - Chen, Song; Lu, Siwei; Sun, Yuelin; Wang, Wenlei; Chen, Yingfu; Li, Jing; Liu, Chengjun (Frontiers in Pediatrics, 2025)
BackgroundA lung abscess is a thick-walled cavity containing purulent material that results from pulmonary infection. It is an uncommon condition that can occur at any age. Bronchopleural fistula (BPF) is a severe complication with a poor prognosis that may arise with the progression of the condition or as a result of treatment.Case presentationWe describe a case of lung abscess complicated by a BPF and septic shock in a 7-year-old girl. A chest tube was inserted and venoarterial extracorporeal membrane oxygenation (ECMO) was emergently used. To selectively block the BPF, an endobronchial blocker was placed in the right intermediate bronchus under bronchoscopic guidance. This approach allowed the BPF to heal, enabled the recruitment of the other lung, and obstructed the purulent fluid. The patient recovered and was discharged after 70 days of treatment.ConclusionsThis case demonstrates that combined endobronchial blocker and ECMO can be an effective approach for patients with lung abscesses and BPFs (especially those aged < 8 years) when the adjustment of conventional therapy is unsuccessful.